THE ROLE OF KOPERASI SYARIAH KHADIJAH AR-ROCHIM SEJAHTERA IN ACCOMMODATING THE SAVINGS AND LOAN NEEDS OF THE SUMBERASRI VILLAGE COMMUNITY - Rangga, Sudharma Ismu Aji; Saksana, Joned Ceilendra (Sekolah Tinggi Ilmu Ekonomi Ganesha, 2025)
Koperasi Syariah Khadijah Ar-Rochim Sejahtera plays a significant role in improving the economic welfare of the residents of Sumberasri through the provision of Sharia-compliant savings and loan services. This article aims to examine the role of this cooperative in meeting the financial needs of the community and to identify the challenges and benefits experienced by the people. This research adopts a descriptive approach combining both qualitative and quantitative methods, through literature review, user satisfaction surveys, and secondary data analysis from the cooperative. The findings show that the cooperative has made a positive impact on economic empowerment, although it faces challenges in management and capital limitations. The main benefits experienced by the members include increased economic welfare, women's empowerment, and strengthened entrepreneurial spirit. This study recommends strengthening management, diversifying businesses, and enhancing members' understanding of Sharia principles to improve the sustainability of the cooperative